2022
DOI: 10.3389/feduc.2022.913390
|View full text |Cite
|
Sign up to set email alerts
|

The Extra-Ordinary Music Camp: An informal online distance learning approach for children with intellectual and physical disabilities and learning disorders

Abstract: In summer 2020, 25 children aged 8–17 with intellectual and physical disabilities and learning disorders participated in a research project called the Extra-Ordinary Music Camp. The objectives were to (1) provide an adapted environment where extra-ordinary children could develop musical creativity; and (2) examine the impact of informal, inclusive, participatory, and adapted creative music activities on specific development areas. Individual 20–40-min online sessions were delivered at a distance biweekly for 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Her recent study (2021) in Hong Kong examines how the curriculum requires teachers to develop music skills, creativity, and imagination in all their students and to achieve the same learning targets for all, regardless of ID status. In the province of Québec (Canada), the Camp musical extra-ordinaire (Després et al, 2022;Després & Grenier, 2021) is an inclusive adapted music program based on principles of informal music learning (Green, 2002(Green, , 2009. The results of Després et al's (2022) study demonstrated that informal learning approaches to music via a synchronous distance learning environment are effective in fostering learner voice and creative expression in children with intellectual and/or physical disabilities.…”
Section: Rationalementioning
confidence: 99%
“…Her recent study (2021) in Hong Kong examines how the curriculum requires teachers to develop music skills, creativity, and imagination in all their students and to achieve the same learning targets for all, regardless of ID status. In the province of Québec (Canada), the Camp musical extra-ordinaire (Després et al, 2022;Després & Grenier, 2021) is an inclusive adapted music program based on principles of informal music learning (Green, 2002(Green, , 2009. The results of Després et al's (2022) study demonstrated that informal learning approaches to music via a synchronous distance learning environment are effective in fostering learner voice and creative expression in children with intellectual and/or physical disabilities.…”
Section: Rationalementioning
confidence: 99%